2017
DOI: 10.1016/j.jdent.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dentine hypersensitivity, dietary acid intake and erosive tooth wear

Abstract: NCT02449434 CLINICAL SIGNIFICANCE: Increased contact time with dietary acids and sipping swishing or holding drinks in the mouth prior to swallowing should be addressed as an aetiological factor in DH. Toothpaste abrasivity and toothbrush filament stiffness may play a greater role in DH compared to frequency of toothbrushing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 18 publications
1
25
1
3
Order By: Relevance
“…Actually, interesting studies aiming to find associated factors for dental hypersensitivity demonstrated a positive trend between TS and dietary acid intake. 21,46 O'Toole and Bartlett 21 demonstrated that dental hypersensitivity is common among patients who consumed acidic drinks 2 or more times a day, as well as acidic drinks between meals without considering the erosive tooth wear, as occurred in the current study. Although the dental hypersensitivity and bleaching-induced tooth sensitivity cannot be confused.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Actually, interesting studies aiming to find associated factors for dental hypersensitivity demonstrated a positive trend between TS and dietary acid intake. 21,46 O'Toole and Bartlett 21 demonstrated that dental hypersensitivity is common among patients who consumed acidic drinks 2 or more times a day, as well as acidic drinks between meals without considering the erosive tooth wear, as occurred in the current study. Although the dental hypersensitivity and bleaching-induced tooth sensitivity cannot be confused.…”
Section: Discussionmentioning
confidence: 51%
“…19,20 In a Dentistry viewpoint, the intake of acidic beverages between meals, such as the cola-based soft drinks demonstrated a significative relation to erosion and, consequently with some degree of dentine hypersensitivity. 21 It was to remember that, the success of bleaching treatment depends of the effectiveness of whitening as well the absence or reduced bleaching-induced tooth sensitivity, 22,23 and considering the growing consumption soft drinks around the world, this clinical trial evaluated whether the effectiveness of bleaching, as well as tooth sensitivity, is affected by exposure to cola-based soft drinks during in-office bleaching treatments using 35% hydrogen peroxide. The null hypotheses are that the exposure to cola-based soft drink during the bleaching treatment will not affect the (1) the effectiveness of bleaching, (2) the absolute risk of bleaching-induced tooth sensitivity and (3) the intensity of bleaching-induced tooth sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ten Cate and Imfeld (1996), tooth erosion is defined by loss of tooth mineral structure through acids agents, without involvement of bacteria, which is a pathological process classified as acute or chronic [13]. Depending on the severity of exposure, there is the possibility of dentin exposure, therefore dentin hypersensitivity, in addition to reduced chewing capacity [9,14]. Once the dentin tissue exposure, there is a necessity for restorative treatments to replace lost tissue [15,16].…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…A camada de esfregaço que veda os túbulos pode ser removida e os túbulos dentinários podem apresentar-se patentes (Addy;West, 1994). Com isso, o paciente pode apresentar sintomatologia dolorosa em sua rotina diária de alimentação e higienização bucal e sabe-se que existe uma relação direta entre desgaste, alimentação ácida e HD (O`Toole; Bartlett, 2017).…”
Section: Introductionunclassified
“…Muitos estudos têm relacionado as LNCs com HD (Olley et al, 2015; O`Toole; Bartlett, 2017;Teixeira et al, 2018). Um estudo realizado no Brasil apresentou relação entre ambas com contato prematuro entre os dentes, ingestão de frutas e sucos de pH ácidos (Yoshizaki et al,2017).…”
Section: Introductionunclassified